Acute burn care in resource-limited settings: A cohort study on treatment and outcomes in a rural regional referral hospital in Tanzania. Issue 8 (December 2022) - Hendriks, T.C.C.; Botman, M.; Binnerts, J.J.; Mtui, G.S.; Nuwass, E.Q.; Meij-de Vries, A.; Winters, H.A.H.; Nieuwenhuis, M.K.; van Zuijlen, P.P.M.
Highlights: In this resource-limited setting patients presented after a delay with multiple complications and a high mortality risk. Delayed skin grafting in survivors of severe burns was found to be safe and effective in this setting. Over time the disability lessened and quality of life improved in the majority of cases. There is room for improvement of the access to timely and safe burn care in underserved populations. Abstract: Background: Only a few papers are published on the safety and effectiveness of acute burn care in low-income countries. A cohort study was therefore carried out to determine such outcomes. Methods: The study was conducted in a rural Tanzanian hospital in 2017–2018. All patients admitted with burns were eligible. Complications were scored during admission as an indication for safety. Survivors of severe burn injuries were evaluated for time of reepithelialization, graft take, disability (WHODAS2.0) and quality of life (EQ5D-3L) up to 3 months post-injury, as an indication of effectiveness. Results: Patients presented on average at 5 days after injury (SD 11, median 1, IQR 0–4). Three patients died at admission. The remaining 79 were included in the cohort. Their median age was 3 years (IQR 2–9, range 0.5–49), mean TBSA burned 12% (SD10%) and mortality rate 11.4%. No surgery-related mortality or life-threatening complications were observed. Skin grafting was performed on 29 patients at a delayed stage (median 23 days, IQR 15–47). Complications of skin grafts included partial (25% of procedures) and complete graft necrosis (8% of procedures). The mean time to reepithelialization was 52 (SD 42) days after admission. Disability and quality of life improved from admission to 3 months after injury ( p< 0.001, p <0.001, respectively). Conclusion: In this resource-limited setting patients presented after a delay and with multiple complications. The mortality during the first two weeks after admission was high. Surgery was found to be safe and effective. A significant improvement in disability and quality of life was observed.